Leishmania braziliensis Infection Enhances Toll-Like Receptors 2 and 4 Expression and Triggers TNF-α and IL-10 Production in Human Cutaneous Leishmaniasis - Polari, Ludmila P.; Carneiro, Pedro Paulo; Macedo, Michael; Machado, Paulo R. L.; Scott, Phillip; Carvalho, Edgar M.; Bacellar, Olívia (Frontiers in Cellular and Infection Microbiology, 2019)
Cutaneous leishmaniasis (CL) caused by infection with Leishmania braziliensis is characterized by an exaggerated inflammatory response that controls the parasite burden, but also contributes to pathology. While myeloid cells are required to eliminate the parasite, recent studies indicate that they may also participate in the inflammatory response driving disease progression. The innate immune response to leishmania is driven in part by the Toll-like receptors (TLRs) TLR2, TLR4, and TLR9. In this study, we used flow cytometric analysis to compare TLR2 and TLR4 expression in monocyte subsets (classical, intermediate, and non-classical) from CL patients and healthy subjects (HS). We also determined if there was an association of either the proinflammatory cytokine TNF or the anti-inflammatory cytokine IL-10 with TLR2 or TLR4 expression levels after L. braziliensis infection. In vitro infection with L. braziliensis caused monocytes to upregulate TLR2 and TLR4 expression. We also found that intermediate monocytes expressed the highest levels of TLR2 and TLR4 and that infected monocytes produced more TNF and IL-10 than uninfected monocytes. Finally, while classical and intermediate monocytes were mainly responsible for TNF production, classical monocytes were the main source of IL-10. Despite the increased expression of TLRs due to leishmania infection and the production of TNF, these patients develop disease, suggesting that TLR expression may be related to pathology in L. braziliensis infection.